Innovation in the Controlled Production of Oyster Mushrooms in Community Greenhouses of Mushroom Producers, Uttaradit Province, Thailand - Kamomkunanon, Siwat; Chutchaidej, Eakruthai; Wittanalai, Suttida; Rangsisuttaporn, Keowalee; Mueangtoom, Kitti; Thanompongchart, Patipat (Area Based Development Research Journal, 2025)
The cultivation of oyster mushrooms is a vital economic activity in ten sub-districts of Uttaradit Province, Thailand, where mushrooms are sold at 40 to 50 baht per kilogram. However, local farmers struggle with crop growth and pest attacks. This is because traditional production facilities can not keep four important environmental conditions in check: 1) the temperature should be between 28°C and 32°C; 2) the relative humidity should be between 70% and 90%; 3) the carbon dioxide (CO₂) level should not be higher than 2,000 ppm; and 4) the light level should not be higher than 100 lux. In response, a large-scale effort was made to improve production facilities by adding new technologies that reduce heat, control light intensity, ventilate excess CO₂, and increase humidity. The project followed a three-step approach: (1) raising awareness and comprehension among farmers, (2) providing education and disseminating knowledge about controlled-environment mushroom cultivation, and (3) upgrading farmers’ mushroom production facilities. After they were finished, all ten greenhouses in the ten sub-districts kept the best conditions for growing plants: temperatures between 28.6°C and 31.7°C, humidity levels between 78.2% and 81.3%, CO2 levels between 285 and 1,365 ppm, and light levels between 51 and 92 lux. Experimental trials conducted in three upgraded facilities demonstrated a yield increase of 25.6% to 26.4% over a 30-day cultivation period. Across all ten facilities, after one full production cycle, yields increased by 21.4% to 33.2%, with an average increase of 26.2%. Additionally, production time decreased by 13.5% to 28.0%, averaging a reduction of 22.5%. Improved environmental control also enhanced the quality of the mushrooms, resulting in more uniform and structurally superior fruiting bodies. The nutritional profile showed that the amount of protein went up from 29.65 ± 2.00% to 31.81 ± 1.16%, which is a 10.94% rise. The amount of antioxidants also went up from 50.54 ± 3.68% to 70.69 ± 2.70%, which is a 39.9% rise. These enhancements significantly improved the marketability of the mushrooms, allowing farmers to increase their selling price to 80 baht per kilogram, representing a price increase of 14.3% to 100%. Consequently, the mushroom-producing community experienced a minimum income boost of 40.5%, enhancing the economic sustainability of their operations. Beyond individual financial gains, this project contributed to broader agricultural development. The establishment of ten prototype greenhouses in the region provided valuable models for other farmers in Uttaradit and neighboring provinces to replicate. In addition, the establishment of two community-based learning centers in the Wang Din and Ban Mo sub-districts provided structured curricula on controlled-environment mushroom cultivation. These centers, managed by trained local innovators, facilitate both theoretical and hands-on training, supported by laboratory equipment and experimental setups. This initiative has empowered local farmers, transforming them into agricultural innovators capable of further refining mushroom production techniques. From an economic perspective, the investment required for greenhouse upgrades, including insulation improvements, humidifiers, and ventilation systems, was approximately 20,500 Baht per facility, with an annual maintenance and utility cost of 2,400 Baht. Given an average production capacity of 3,000 mushroom logs per cycle, farmers realized an annual net income increase of 74,600 Baht (or 24,800 Baht per cycle). Financial analysis indicated a payback period of approximately five months, with a net present value (NPV) of 290,780 Baht and an internal rate of return (IRR) of 363%, underscoring the economic feasibility of this investment. Socially, the project fostered a paradigm shift in mushroom farming, promoting the adoption of controlled-environment agriculture among local growers. Initially, farmers required close guidance to integrate and manage technological improvements effectively. However, as they became proficient, their confidence in these technologies grew, reinforcing the benefits of precise environmental control. There are six main parts to the new learning and innovation platform (LIP) that make it easier for knowledge to be shared: 1) lead innovators trained through the research initiative; 2) assistant instructors helping to teach the curriculum; 3) classrooms set aside in greenhouses; 4) structured teaching materials created through knowledge management processes; 5) experimental labs in community greenhouses; and 6) the tools needed for hands-on training. This structured approach ensures ongoing skill development and innovation in mushroom farming. Overall, this project has significantly improved oyster mushroom production in Uttaradit Province through strategic facility enhancements and farmer education. The combination of increased yields, improved mushroom quality, reduced production time, and economic viability underscores the potential for wider adoption of controlled-environment agriculture in Thailand and beyond. The establishment of prototype greenhouses and community learning centers further strengthens knowledge-sharing mechanisms, ensuring long-term sustainability and continuous innovation in the sector.